Nymphaea “Eldorado” flower extract targets serpine 1 to attenuate inflammatory and antioxidant crosstalk in zebrafish - Liyan Mao; Liyan Mao; Lingyun Long; Lingyun Long; Qian Qin; Qiuwei Huang; Qiulan Huang; Yanping Yu; Liqiong Ding; Gongde Liu; Ji Zhang; Ji Zhang; et al. (Frontiers in Pharmacology)
Chronic inflammation and oxidative stress are pivotal drivers of pathological conditions, necessitating safer plant-derived therapeutic alternatives. This study elucidates the anti-inflammatory and antioxidant mechanisms of Nymphaea “Eldorado” flower water extract (NEWE) in a zebrafish (Danio rerio) model of copper sulfate (CuSO4)-induced inflammation. NEWE (25–100 μg/mL) attenuates CuSO4-triggered neutrophil migration and oxidative stress by downregulating proinflammatory genes (il1b, ptgs2a/b) and reducing reactive oxygen species (ROS) production. Transcriptomic profiling identified 339 differentially expressed genes (DEGs), enriched in cytokine signaling and redox regulation, with serpine1, stat3, and mmp9 emerging as key regulatory hubs. Widely targeted metabolomics revealed 891 bioactive compounds, including flavonoids and phenylpropanoids, with network pharmacology predicting multi-target interactions involving inflammatory and oxidative stress pathways. Molecular docking confirmed binding affinities between protocatechuic acid, L-pyroglutamic acid, and Serpine1’s active site, indicating direct interference with inflammation modulation. Collectively, these results establish NEWE as a polypharmacological agent that disrupts inflammation-oxidative stress crosstalk primarily through Serpine1-mediated pathways, offering a molecular foundation for plant-derived interventions against chronic inflammatory diseases.